(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
In the modern healthcare system, a specialist engaged in professional activity is required not only to have deep theoretical knowledge but also a high level of practical skills, communication culture, clinical thinking, and the ability to make independent decisions — that is, a set of complex professional competences. Especially, the work of medical personnel, which is directly related to the life and health of patients, requires the continuous development of these competences. Competence is a term widely used in modern literature today, encompassing such pressing issues as education, staff selection, assessment of work results, the success of education, students’ career orientation, and the like.